Analysis Analysis of Histogram and Grayscale on Chest X-Ray Computed Radiography Image in Covid-19 Disease vs Normal - Utami, Hernastiti Sedya; Rahmawati, Ika Mentari Putri; Reski, Rifdatul (Jurnal EduHealth, 2022)
Chest X-ray the main imaging modality for diagnosing Covid-19. An optimal radiograph is needed, so that it can be used as a support for the diagnosis of the disease. The use of digital CR can produce images easily, quickly, optimally, and can be processed as needed. However, it is possible that clinical acquisitions can result in low quality digital images. CR digital images can calculate grayscale and histogram values and can provide clues in diagnosing patients in Covid-19 cases by analyzing that values. Each covid-19 and normal group as many as 18 CXR postero-anterior projection images analyzed by quantitative analysis was conducted by measuring the mean of grayscale values and displayed histogram use ImageJ software. The result is there is a significant difference in the mean grayscale value between normal and covid-19 chest images (p<0.001). The grayscale value in the covid-19chest image (117.433±4.314) has a higher grayscale value and histograme range that is more inclined to the right than the normal chest image (65.231±3.304). Finally, histogram and grayscale values are very helpful in establishing the diagnosis of Covid-19.